2013
DOI: 10.1038/srep01636
|View full text |Cite
|
Sign up to set email alerts
|

I want to lie about not knowing you, but my precuneus refuses to cooperate

Abstract: Previously identified neural correlates of deception, such as the prefrontal, anterior cingulate, and parietal regions, have proven to be unreliable neural markers of deception, most likely because activity in these regions reflects executive processes that are not specific to deception. Herein, we report the first fMRI study that provides strong preliminary evidence that the neural activity associated with perception but not executive processes could offer a better marker of deception with regard to face fami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
22
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 46 publications
4
22
0
Order By: Relevance
“…Precuneus activity has been reported in fMRI studies of face processing (metaanalysis in Fusar-Poli et al, 2009), and has specifically been associated with social recognition (Lee et al, 2013). In general, the precuneus is thought to play a role in self-awareness and higher cognitive processes above and beyond sensory discrimination (reviewed in Cavanna and Trimble, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Precuneus activity has been reported in fMRI studies of face processing (metaanalysis in Fusar-Poli et al, 2009), and has specifically been associated with social recognition (Lee et al, 2013). In general, the precuneus is thought to play a role in self-awareness and higher cognitive processes above and beyond sensory discrimination (reviewed in Cavanna and Trimble, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Research on the precuneus has accelerated in the past decade due to development of non-invasive medical imaging techniques, namely MRI, fMRI, and PET. Functional studies have revealed that the precuneus is involved in a variety of functions associated with self-perception and visual imagery [Lou et al, 2004; Land, 2014], processing of spatial working memory [Wallentin et al, 2006, 2008], and memory retrieval (recognition of familiar faces [Gobbini and Haxby, 2007; Lee et al, 2013]; episodic memory [Vannini et al, 2011]; recognition memory [Hassabis and Maguire, 2009] autobiographical memory [Freton et al, 2014]). Moreover, the precuneus is a functional core of the Default Mode Network, a set of interconnected cortical areas that is active at rest [Raichle et al, 2001; Tomasi and Volkow, 2010; Utevsky et al, 2014], and it is a crucial hub of large-scale brain connectivity [Hagmann et al, 2008; Li et al, 2013; Reus et al, 2014].…”
Section: Introductionmentioning
confidence: 99%
“…To provide a better marker of deception that differs from executive functions, Lee et al (2013) focused on perceptual functions. During a Face Recognition task, participants were instructed to lie about the familiarity of a set of photos: the faces of individuals who were personally familiar to the participants and the faces of unfamiliar persons.…”
Section: Other Correlates Of Deceptionmentioning
confidence: 99%